THE CONCEPT OF TOLERANCE IN MARRIAGE AND FAMILY RELATIONS ACCORDING TO ISLAM - Annajah Zelviana, Zulfa; Eren, Sadi (El-Furqania : Jurnal Ushuluddin dan Ilmu-Ilmu Keislaman, 2024)
It is impossible to be separated from the family in a person's life and life, because it is here that the beginning of social life takes place. The family is the smallest but most important unit of society. The family is a small social group consisting of father, mother and children, in which love, affection and responsibility are shared in a just manner, so that parents and children can Islamically control their behaviour, think and act in a social spirit. All family members have a sense of family responsibility. Thus, they become a good Muslim family, faithful to their worship and tolerant towards society. This research is a qualitative research conducted by literature review method by applying content analysis with books and articles that examine the concept of tolerance in the family according to Islam. This research aims to provide lessons and information about the meaning of building a beautiful family in Islam. It also aims to show how a husband, wife and children can properly care and concern for each other with love and compassion in accordance with Islam and the Sunnah of the Prophet. Key words: Qur'an, tafsir, family, tolerance, social.